An outline on the jurassic in colombia (1984)
The main objective of this summary is to provide information about the more important advances achieved during last ten years in Jurassic studies in Colombia, and to present the corresponding bibliographic references. It is not intended to undertake a complete review of papers as well known to the geologic community as those by Renz (in Trumpy 1943), Nelson (1957), Hubach (1957), Burgi (1960, 1964), Cediel (1968, 1969), and Barrero (1969).